Development Of Health Service Module Based On Islamic Values For 4-5 Years Old Children - Fitri Hidayah; Masganti Sit; Fibri Rakhmawati (Tadrib: Jurnal Pendidikan Agama Islam, 2024)
This study aims to develop a health service module based on Islamic values in children aged 4-5 years. The module development was conducted through five stages, namely analysis, design, development, implementation, and evaluation, with the application of the ADDIE model. Module validation was conducted by health, design, and language experts to ensure its feasibility and quality. The development of health service modules based on Islamic values for children aged 4-5 years proved to be effective based on the results of validation and effectiveness tests. Module validation by health, module/design, and language experts showed excellent results, with a final score above 97% from all three experts. Module implementation was conducted in two educational institutions, RA Banatus Shalih and RA Rabiatul Adawiyah, through parenting activities. The test results showed a significant increase in children's understanding of health. In RA Banatus Shalih, the pre-test average score rose from 57.5 to 93.75 with an N-Gain of 8.85, while in RA Rabiatul Adawiyah the pre-test score rose from 58.125 to 87.5 with an N-Gain of 0.70. This shows that the module is very effective in improving children's understanding of health.